2020
DOI: 10.21608/asnj.2020.47528.1062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Program about Head nurses Authentic Leadership Style on Staff Nurses Empowerment and Motivation

Abstract: Background: Nurses form the largest group of healthcare professionals and are on the front-line of care for patients in hospitals. More excellent patient outcomes result from nurses working in a supportive setting. Organizational leaders necessity to demonstrate trust and independence to encourage nurse motivation, as these behaviors are congruent with intrinsically held nursing values. Authentic leadership has been introduced as the root element of productive leadership needed to develop healthier work enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Consequently, understanding such approach in the context of the healthcare sector may in turn, help for establishing new links between leaders and their subordinates to enable them to provide high quality patient care and enhance their professional practice to improve the organization's effectiveness and success. As a result, authentic leadership development, a subset of positive leadership, must be prioritized (Nagib, Rashed & El-Said, 2020). Also, the impact of authentic leadership on nurses' resilience and innovation has rarely been addressed in leadership context (Okmen, Elci, Murat & Yilmaz, 2018).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Consequently, understanding such approach in the context of the healthcare sector may in turn, help for establishing new links between leaders and their subordinates to enable them to provide high quality patient care and enhance their professional practice to improve the organization's effectiveness and success. As a result, authentic leadership development, a subset of positive leadership, must be prioritized (Nagib, Rashed & El-Said, 2020). Also, the impact of authentic leadership on nurses' resilience and innovation has rarely been addressed in leadership context (Okmen, Elci, Murat & Yilmaz, 2018).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…This result, in the same line with Alilyyani [25], found that the majority of head nurses had moderate levels of total authentic leadership skills. This result contradicted with Ali et al [ 27] , found that threequarters of head nurses had low total authentic leadership skills, disagreed with Nagib et al [28] , and found that more than three-quarters of head nurses had low authentic leadership skills. At the same time, only a minority had a high authentic leadership skills in the pre-test.…”
Section: Discussionmentioning
confidence: 67%